2022
DOI: 10.3390/ijerph19042228
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness and Inflammatory Response to the Training Load of Wheelchair Rugby Players

Abstract: The aim of the study was the evaluation of the hormonal response of wheelchair rugby participants under the half-year training cycle. The study sample included 11 members of the Polish national wheelchair rugby team with spinal cord injury at the cervical level, ranging in age from 21 to 41 years, body weight (72.2 ± 11.53 kg), and body height (182.3 ± 6.11 cm). The disabled individuals with spinal cord injury subjected to the study constitute a homogeneous group in terms of age, body height, weight, and injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Despite the growing number of individuals with other impairments, WR remains predominantly dominated by athletes with cervical-level spinal cord injuries (tetraplegia). 16 This type of injury has primarily of traumatic origin, meaning it is acquired. 17 A recent study assessing various Paralympic sports found that the mean age for athletes with acquired impairments to transition to the elite phase was 36.8 (7.9) yrs; in contrast, it was 29.3 (6.1) yrs for athletes with congenital impairments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing number of individuals with other impairments, WR remains predominantly dominated by athletes with cervical-level spinal cord injuries (tetraplegia). 16 This type of injury has primarily of traumatic origin, meaning it is acquired. 17 A recent study assessing various Paralympic sports found that the mean age for athletes with acquired impairments to transition to the elite phase was 36.8 (7.9) yrs; in contrast, it was 29.3 (6.1) yrs for athletes with congenital impairments.…”
Section: Discussionmentioning
confidence: 99%
“…The consistency in age across this sport may be attributed to a significant characteristic of WR players: the acquired condition of their impairment. Despite the growing number of individuals with other impairments, WR remains predominantly dominated by athletes with cervical-level spinal cord injuries (tetraplegia) 16 . This type of injury has primarily of traumatic origin, meaning it is acquired 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Six studies (n = 354 participants) included observational longitudinal data and assessed changes in CRF outcomes following either standard of care inpatient rehabilitation [99][100][101] or a period of community free-living [99,102,103]. While 1 study described a training programme for elite-level wheelchair rugby players, it could not be determined whether players adhered to the prespecified training programme throughout the season, and therefore, the study was categorised as a community free-living observational study in this review [104]. The duration between assessments for standard of care varied, ranging from 5 to 28 weeks, whereas the follow-up period for community observations ranged from 30 weeks to 2.9 years.…”
Section: Plos Medicinementioning
confidence: 99%